492. Canadian consensus of COVID-19 policy and management aspects. (31st December 2020) - Tsang, Kara; Mertz, Dominik; Chagla, Zain; Smaill, Fiona; Khan, Sarah
Abstract: Background: As evidence rapidly changes, a need for consensus in hospital policy and management aspects of COVID-19 patient care are needed. This study describes areas where consensus exists and is needed in infection control, and occupational health policy. Methods: An online survey was sent to the membership of the Association of Medical Microbiology and Infectious Disease (n~700). The survey included questions about COVID-19 patient and outbreak management, personal protective equipment (PPE), and occupational health considerations. Results: Our preliminary results (n=24) were from infectious disease MD/NP or infection control medical directors. All respondents agreed treatment of COVID-19 patients should only occur in the context of a clinical trial. Of 18 centers with neonatal populations, the majority (64.2%) did not have any neonatal specific treatment guidelines. Well-babies born to COVID-19 positive moms, are all being tested (10 of 10 respondents). Variation in practice on when to remove a patient from additional precautions and potential aerosol generating medical procedures (Table 1, 2). Universal masking is in place for all clinical staff (100%), non-clinical staff (70.8%), essential visitors or patient caregivers (70.8%), and universal eye protection is in place for clinical staff (93.3%), but there was a lack of consensus in PPE conservation strategies (Table 3). Most staff do not use neck PPE (68.2%), however there was comments of it being requested by anesthesiologists at 2 sites (Table 2). Healthcare trainees or workers in these groups were restricted from caring for COVID-19 patients; Age >65 years (54.5%) and immunocompromised status (54.5%). COVID-19 positive staff can return to work 14 days after symptom onset (84.2%). Table 1. Areas of COVID-19 management lacking consensus. Not all respondents answered every question. The percentage in brackets was calculated with the number of respondents per question as the denominator. Table 2. Procedures considered as aerosol generating medical procedures (AGMPs). Respondents (n=24) were allowed to select more than one option. Table 3. Personal protective equipment (PPE) conservation strategies (n=24). Not all respondents answered every question. The percentage in brackets was calculated with the number of respondents per question as the denominator. NA corresponds to the question not asked in the survey. Conclusion: Across Canada, while there are areas of consensus in outbreak definitions, universal masking of clinical staff. There is significant variation in practice with respect to discontinuing additional precautions or outbreak measures, asymptomatic testing, AGMP definitions, PPE conservation strategies including reprocessing. As evidence evolves, national infection control guidelines will be important to improve standardization of practice and optimize patient care and staff safety. Disclosures: All Authors : No reported disclosures